Cloud Assessment Learning Environment - Steele, A.; Rickards, Anthony (CITRENZ, 2014)
This paper presents an investigation into student perceptions of the cloud assessment learning environment. The cloud assessment learning environment is a unique learning environment made possible by the recent advent of cloud computing and the associated technologies. The research questions addressed in this focus on how students engage with the environment, the factors of the environment that students perceive as either positive or negative, and also the conceptual change in student understanding of the environment. In order to investigate student perceptions of the cloudassessment learning environment a multi-method ethnographic case study approach was utilised for the study. Findings are presented on a number of key features of the cloud assessment learning environment, these include: lecturer monitoring, google docs as a tool, the feedback mechanism, cloud storage, and technology preference. In addition, findings relating to how students engage with the environment are also presented.